TIPOLOGI KODIFIKASI HADITH DALAM KITAB TUá¸¤FAT AL Aá¹¢RÄ€F BI MAâ€™RIFAT AL-Aá¹¬RÄ€F - Aniqoh, Aniqoh (IAIN Kediri, 2017)
book AÃ¡Â¹ÂrÃ„Âf is one of the book that can be used to help in studying hadith, especially if muhaddith want to conduct takhrij al-hadith that can be used as dictionary in looking for sanad hadith. It is also the hadith book that is summarized by the author to mention the previous hadith and show the next lafal hadith. The basic reason of the book written is to collect many hadith in kutÃ…Â«b al sittah and some of their Mulhaq easily that can be read appropriately based on the sequence of their various sanad in order to put them in one place. The author mentions previously some hadith having most widely tarjamah (meaning). As six riwayah is previously used than five riwayah; the five riwayah is used previously than the four riwayah and soon. The types of hadith book, AÃ¡Â¹ÂrÃ„Âf, have special thing besides their obstacles faced when they are used in takhrij hadith. Keywords: KitabTuhfat, takhrij al-hadith,Hadith